Negative reciprocity and its relation to anger-like emotions in homogeneous and heterogeneous groups - Marianna Bicskei; Matthias Lankau; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
Several studies have shown that social identity fosters the provision of public goods and enhances the willingness to reciprocate cooperative behavior of group members dependent on the social environment. Yet, the question of how social identity affects negative reciprocity in identityhomogeneous and -heterogeneous groups has received only little attention. Consequently, we seek to fill this gap by examining whether social identity affects individuals' willingness to sanction deviating group members in a public good context. Moreover, we devote particular attention to the role of anger-like emotions in negative reciprocity. To test our hypotheses we employ one-shot public good games in strategy method with induced social identity. Our results indicate that members of identity homogeneous groups punish much less often and in smaller amounts than of identity heterogeneous groups when they face contributions smaller than their own. We also find that anger-like emotions influence punishment behavior much stronger when individuals are matched with members of different identities than in identity homogenous groups. These findings contribute to the better understanding of the nature of social identity and its impact on reciprocity, improving economists ability to predict behavior taking emotions also into consideration.
Keywords: 330; social identity; emotions; experiment; public goods; negative reciprocity